Avaliação dos efeitos da placa estabilizadora de oclusão na distribuição de tensões no disco da articulação temporomandibular, pelo método de elementos finitos - Ferreira, Fabiane Maria (2017)
Temporomandibular disorder (TMD) is a term that refers to signs and symptoms associated with pain and functional and structural disturbances of the masticatory system, especially muscles, temporomandibular joints (TMJs) and surrounding tissues. This disorder is considered the most frequent cause of chronic orofacial pain, 40% to 75% of healthy individuals point out at least one sign and 33% observed at least one symptom of TMD. Conservative approaches, including occlusal splint therapy, is the first option to treat temporomandibular disorders (TMD), due to its high efficacy associated with the possibility of reversibility and low morbidity.The action of the splints in the intraarticular space is still discussed, but is considered that the occlusal splints leads to reduction of stress in the temporomandibular joint secondary to change in the position of the mandible. Thus, the general objective of the present study was to evaluate the influence of occlusal stabilization splint on stress and strain generation in the temporomandibular joint disc, under conditions of normality and anterior disc displacement, using the finite element analysis. This study involved three speci fic objectives. Objective 1: analyze the effect of the occlusal splint on stress distribution on the temporomandibular joint disc, in different positions. Objective 2: to know the properties used for articular disc in other FEA studies by means of a bibliographic survey of the literature, and based on this, develop an accurate 3D computational model of a normal TMJ, by the Materialise Interactive Medical Image Control System (MIMICS). Objective 3: develop 3D computational models, of normal TMJ, in order to simulate mandibular closure in the presence or absence of an occlusal splint to evaluate the distribution of stress and strain in both situations. The methods used were 2D and 3D finite element analysis and stress evaluation by von Mises criterion, and literature review. Based on the results of these objectives is possible to conclude that in all tested situations the lower surface of the disc exhibited the higher concentration of stresses and strain, and in the anteroposterior analysis the most affected region was the intermediate zone of the disc. When the disc is displaced anteriorly, although the splint does not promote a great reduction in the stress magnitude, a tendency of reduction has been observed that should be better investigated in future studie s. Bilateral and 7 3D analysis of the TMJs revealed that although the splint does not provide a significant stress and strain reduction, it promotes better occlusion stabilization reflecting in better stabilization of the joints. Thus, they work more symmetr ically and the stresses are distributed between the two discs homogeneously. Finally, the literature review on the mechanical properties of the articular disc revealed that although it is predominantly viscohiperelastic, there are many ways to characterize the disc and that each representation has its particularities and limitations that must be considered when interpreting the results.